2022
DOI: 10.1186/s12917-022-03159-x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of brucellosis, Q fever and Rift Valley fever in domestic ruminants in Guinea in 2017–2019

Abstract: Background Brucellosis, Q fever and Rift Valley fever are considered as Neglected Zoonotic Diseases (NZDs) leading to socioeconomic losses in livestock globally, and particularly in developing countries of Africa where they are under-reported. In this study, we evaluated the seroprevalence of these 3 zoonotic diseases in domestic ruminants in Guinea from 2017 to 2019. A total of 1357 sera, sampled from 463 cattle, 408 goats and 486 sheep, were collected in 17 Guinean prefectures and analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
14
1
1
Order By: Relevance
“…burnetii , despite their single occurrence in the same wildlife populations. Nevertheless, this coinfection was reported in domestic animals in Guinea [ 32 ] and therefore, we cannot entirely rule out the possibility of co-exposure to the two pathogens in wild species. Further, our ongoing unpublished studies have also identified Brucella and C .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…burnetii , despite their single occurrence in the same wildlife populations. Nevertheless, this coinfection was reported in domestic animals in Guinea [ 32 ] and therefore, we cannot entirely rule out the possibility of co-exposure to the two pathogens in wild species. Further, our ongoing unpublished studies have also identified Brucella and C .…”
Section: Discussionmentioning
confidence: 88%
“…Our study found no evidence of co-exposure to Brucella and C. burnetii, despite their single occurrence in the same wildlife populations. Nevertheless, this coinfection was reported in domestic animals in Guinea [32] and therefore, we cannot entirely rule out the possibility of co-exposure to the two pathogens in wild species. Further, our ongoing unpublished studies have also identified Brucella and C. burnetii co-exposure in livestock belonging to the Bovidae family, to which some wildlife species investigated here belong.…”
Section: Co-exposure With Any Of the Three Pathogensmentioning
confidence: 81%
“…Of the 388 eligible articles, 183 were excluded for multiple reasons described in Figure 1. Finally, a total of 205 articles (629 data on prevalence and/or CFR) met the inclusion criteria for this systematic review (Abakar et al, 2014;Abdallah et al, 2016;Adamu, 2020;Adamu et al, 2021;Adesiyun et al, 2020;Ahmed et al, 2018Ahmed et al, , 2020Alhaji, 2020;Andayi et al, 2014;Andriamandimby et al, 2010;Andriamandimby et al, 2018;Aradaib et al, 2013;Archer et al, 2011Archer et al, , 2013Atuman et al, 2022;Ayari-Fakhfakh et al, 2011;Ba et al, 2012;Baudin et al, 2016;Beechler et al, 2015;van den Bergh et al, 2022;Spiropoulou & Nyakarahuka, 2018;Sternberg Lewerin, 2018;Stoek et al, 2022;Sumaye et al, 2013Sumaye et al, , 2015Swai & Schoonman, 2009;Swai & Sindato, 2015;Tigoi, 2020;Tigoi et al, 2015;Traoré-Lamizana et al, 2001;Troupin et al, 2022;Tshilenge et al, 2019;Umuhoza et al, 2017;Ushijima et al, 2021;van den Bergh et al, 2020;Wensman et al, 2015;Wolff et al, 2018;Woods et al, 2002;Youssef, 2001Youssef, , 2009…”
Section: Results Of the Study Searchmentioning
confidence: 99%
“…Brucella (particularly Brucella melitensis), Toxoplasma and Leptospira species are zoonotic pathogens transmissible during processing of infected goat carcasses [14][15][16][17][18]50]. Apart from these pathogens, Q-fever, Orf and Rift valley fever viruses can spread from infected goats to humans during handling/slaughter [51][52][53]. In Nigeria, the chances of contamination of the processed meat and or infection of slaughterhouse workers with these zoonotic pathogens are high; considering the unsanitary conditions of the slaughter facilities and non-use of personal protective equipment by the workers during abattoir operations [50].…”
Section: Plos Onementioning
confidence: 99%